1990
DOI: 10.1111/j.1365-3180.1990.tb01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Diclofop‐methyl antagonism by broadleaf weed herbicides: the importance of leaf expansion rate

Abstract: Summary: Avena saliva cv. Amuri and A. fatua were sprayed with diclofop methyl (1.0 kg a.i. ha−1) alone and in combination with 2,4‐D (1.1 kg a.i. ha−1), bentazone (1.0 kg a.i. ha−1), chlorsulfuron (15 g a.i. ha−1) or dicamba (0.3 kg a.i. ha−1). Effects of the herbicides on leaf extension rate during the first 8 to 10 days after spraying and subsequent growth (dry weight) after 57–75 days were determined by comparison with unsprayed plants. Diclofop‐methyl applied alone did not cause a decrease in leaf extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…Therefore, depending on the spray date, these growth rates represent approximately three-or fourfold differences in wild oat growth rates. Andrews (1990) found that the most rapidly expanding wild oat leaf grew approximately 30 mm/d. At Lethbridge in 1996, wild oat growth rates increased from 8 mm/d on July 4 to 20 mm/d on July 5 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, depending on the spray date, these growth rates represent approximately three-or fourfold differences in wild oat growth rates. Andrews (1990) found that the most rapidly expanding wild oat leaf grew approximately 30 mm/d. At Lethbridge in 1996, wild oat growth rates increased from 8 mm/d on July 4 to 20 mm/d on July 5 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, wild oat control with 100 g/ha of imazamethabenz increased only 6% for every 10 mm of wild oat growth in the 24 h preceding herbicide application (data not shown). Andrews (1990) found that some broadleaf herbicides reduce wild oat leaf extension rate (growth) faster than diclofop. He postulated that decreased wild oat growth rate during the first few days after spraying is the cause of broadleaf-herbicide antagonism of diclofop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional hypothesis to explain the antagonistic effect of auxin-like herbicides on the activity of diclofop was provided by Andrews (2). He showed that 2,4-D and dicamba (3,6-dichloro-2-methoxybenzoic acid) caused a rapid and significant reduction in the rate of leaf extension in wild and cultivated oats.…”
Section: Antagonistic Effects Of Auxin Herbicidesmentioning
confidence: 99%
“…The mechanisms responsible for herbicide antagonism have been classified by Hatzios and Penner (1985) as biochemical, competitive, physiological andlor chemical. Antagonism of postemergence graminicides (aryloxyphenoxy propionic acids and cyclohexanediones) used for grass weed control in combination with sulfonylureas is well-documented (Baerg et al, 1996;O'Sullivan & Kirkland, 1984;Liebl & Worsham, 1987;Andrews, 1990). According to Penner ( 1989) adjuvants can affect herbicide antagonism in at least two ways, namely to increase herbicide absorption directly and to prevent the formation of less preferred absorption forms of weakly acidic herbicides.…”
Section: Introductionmentioning
confidence: 99%